Nutritional Intake of Children in Kebon Pala East Jakarta - Lisnaini Lisnaini; Weeke Budhyanti; Meliana Chandra (Universitas Ahmad Dahlan, 2023)
Background: A mother is the main nutrition provider of an Indonesian family. Their own health profiles and situations may affect their abilities to provide proper nutrition. In this research, we try to find mothers in Kebon Pala profile, and the nutrition taken by their children; Method: This quantitative descriptive study was conducted by using a self-administered questionnaire which has been responded to by 94 mothers in Kebon Pala. This research was conducted from October 2021-April 2022. Results: 61.54% child takes 3 times carb intake a day, but unlike the national nutritional guidelines, only 20% take anima-based protein 3 times a day, only 34.83% take plant-based protein 3 times a day, and only 33.33% take vegetable 3 times a day. This minimal variation of plate filling happened, even though 49.44% child never complained about the food available and 55.56% child never complained about vegetables/fruit on their plate. Conclusion: Children in Kebon Pala did not eat balanced nutrition meals, and most of them have eating difficulties (fussy eaters).